ASESMEN UNJUK KERJA PORTOFOLIO DALAM MENULIS TEKS PERSUASI KELAS VIII SMP NEGERI 16 KOTA JAMBI - Dila Nurzafti, Kharisma; Nazurty, Nazurty; D., Yusra; Purba, Andiopenta (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
This study was used a qualitative-descriptive approach to purposely figuring the application of assesment in the performance of writing persuasive text for VIII grade of SMP Negeri 16 Jambi City in 2022/2023 Academic Year. The students and the teacher in class VIII become the subjects of this study during the class. Data collection techniques were carried out by interviews, observations, and also documentation of the subjects and objects of the research. The data used in this research is the application of performance assesment in writing persuasive text for VIII grade of SMP Negeri 16 Jambi City. The result of this study shows that the application of performance assesment in writing persuasive text was applied well according to assesment standard of Curiculum 2013, with the RPP, indicators, and the given tasks to students are mutually sustainable. The application of this performance assesment was met the obstacles caused by the internal factors, such as limited study time and motivation lacks students to studying.